Heme-Regulated eIF2α Kinase Modulates Hepatic FGF21 and is Activated by PPARβ/δ Deficiency - Zarei, Mohammad (2016)
Fibroblast growth factor 21 (FGF21), a peptide hormone with pleiotropic effects on carbohydrate and lipid metabolism, is considered a target for the treatment of diabetes. In this study, we investigated the role of Peroxisome Proliferator-Activated Receptor (PPAR)β/δ deficiency in hepatic FGF21 regulation. Increased Fgf21 expression was observed in liver of PPARβ/δ-null mice and in mouse primary hepatocytes when this receptor was knocked down by small interfering RNA (siRNA). Increased Fgf21 was associated with enhanced protein levels in the heme-regulated eukaryotic translation initiation factor 2α (eIF2α) kinase (HRI). This increase caused enhanced levels of phosphorylated eIF2α and activating transcription factor (ATF) 4, which is essential for Fgf21-induced expression. siRNA analysis demonstrated that HRI regulates Fgf21 expression in primary hepatocytes. Enhanced Fgf21 expression attenuated tunicamycin-induced endoplasmic reticulum stress, as demonstrated by using a neutralizing antibody against FGF21. Interestingly, increased Fgf21 expression in mice fed a HFD or hepatocytes exposed to palmitate was accompanied by reduced PPARβ/δ and activation of the HRI-eIF2α-ATF4 pathway. Moreover, pharmacological activation of HRI increased Fgf21 expression and reduced lipid-induced hepatic steatosis and glucose intolerance and these effects were not observed in Fgf21-null mice. Overall, these findings suggest that HRI is a potential target for regulating hepatic FGF21 levels.